2022
DOI: 10.1186/s13098-022-00935-5
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the hepatoprotective, hypolipidemic, and antidiabetic impacts of aliskiren in streptozotocin-induced diabetic liver disease in mice

Abstract: Background Diabetic hepatopathy is a serious complication of poorly controlled diabetes mellitus. An efficient antidiabetic drug which keeps normal liver tissues is not available. The renin-angiotensin system has been reported to be involved in both diabetic state and liver function. Aliskiren is a direct renin inhibitor and a recently antihypertensive drug with poly-pharmacological properties. The aim of the current study is to explore the possible hepatoprotective effects and mechanisms of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…STZ treatment caused significant damage to the liver by altering hepatocyte structures, causing hepatomegaly, dilation of hepatic sinusoid capillaries, apoptosis, increased adipogenesis and cell death in hepatocytes. Besides, STZ treatments also induced signs of inflammation in the liver, which needed to be reversed or stabilized in order to combat diabetes [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…STZ treatment caused significant damage to the liver by altering hepatocyte structures, causing hepatomegaly, dilation of hepatic sinusoid capillaries, apoptosis, increased adipogenesis and cell death in hepatocytes. Besides, STZ treatments also induced signs of inflammation in the liver, which needed to be reversed or stabilized in order to combat diabetes [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cornelia G Bala et al found that the disruption of the tyrosine biosynthesis pathway might be disrupted related to the high oxidative stress response in patients with type 2 diabetes (38). Oxidative stress is a key pathogenic factor in diabetic complications and can lead to the development of microangiopathy and ASCVD (39,40). Changes in metabolite levels may reflect the occurrence of multiple pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of amide synthesis, since α -substituted aliphatic chiral amides are common substructures across bioactive compounds like Aliskiren 340 , 341 , 342 , 343 and Cebulactam A 344 , 345 , 346 , efficient α -enantiopure amides synthesis methods and late-stage application require further development.…”
Section: Nitrogenation Of Bioactive Compoundsmentioning
confidence: 99%